Propuestas para introduccíon de nanociencia y nanotecnología en escuelas pre universitarias - Ribeiro, Allan Victor (2013)
Effective pedagogical practices for teaching Nanoscience and Nanotechnology in the pre-university education are suggested. The proposals are based on the scientific and didactical experience of the authors, on the study of the available literature and on a diagnosis of the knowledge and interest of the students. Which was conducted at a pre-university school in the city of Bauru, SP, Brazil.